Coupling phosphonate oxidation and phosphate sequestration via Cu-La dual sites in La-based layered carbonate hydroxide - Jinbin Lin; Bo He; Yuli Ma; Xue Li; Yan Wei; Baoxue Zhou; Mingce Long (Water Research, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Differential light spectrum regulation of oogenesis and spermatogenesis in Plectropomus leopardus - Hui Ding; Lin Li; Da Zheng; Mingjian Liu; Jinyang Xie; Binglin Li; Yuli Li; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Bimetallic synergy-driven S-scheme MIL-125(Ti)@Ce-Ni heterojunction for efficient visible-light photocatalytic degradation - Peiliang Xie; Xiaoyan Wu; Lin Lin; Ziyu Wang; Jie Xu; Yuli Ma; Jun Zhu; Qin Tong (Journal of Environmental Chemical Engineering, 2026)

Multinational enterprises mitigate carbon inequality across Chinese cities - Kang Lin; Kailan Tian; Yuli Shan (Sustainable Production and Consumption, 2026)

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Bisphenols and parabens in soils and outdoor dust from a metropolitan city in the Guangdong–Hong Kong–Macao Greater Bay Area, China: concentrations and human exposure risk - Xulong Chen; Xiujuan Qi; Bingjun Lu; Yuli Lin; Bo Fu; Chiqun Shan; Xiangxuan Kong; Kai Lin; Tingting Zhu; Shaoyou Lu (Environmental Monitoring and Assessment, 2026)

Arsenic species in crayfish from the Yangtze River basin, China: Levels composition and health risk assessment - Xinjie Li; Bo Fu; Kai Lin; Jiayin Huang; Sisi Yu; Wenchao Zhu; Yuli Lin; Chiqun Shan; Mingqin Zhong; Shaoyou Lu (Aquaculture, 2026)

Occurrence, distribution, and potential risk of per- and polyfluoroalkyl substances in soil, outdoor dust, and atmospheric particles in the electronic industrial agglomeration zone in South China - Hanying Zheng; Xulong Chen; Bingjun Lu; Pei Luo; Bei Wang; Chiqun Shan; Bo Fu; Yuli Lin; Muchen Yin; Jiayi Xu; Xiangxuan Kong; Tingting Zhu; et al. (Environmental Pollution, 2026)

Optimal matrix identification of parabens, triclosan and triclocarban for biomonitoring: Comparative analysis in urine, whole blood, serum, and plasma - Weizhong Chen; Yuli Lin; Kai Lin; Xiaoru Wu; Chiqun Shan; Bo Fu; Yiran Chen; Junye Bian; Xinjie Li; Xulong Chen; Tao Chen; Guangyu Sun; et al. (Journal of Hazardous Materials, 2025)

AdaptVFMs-RSCD: Advancing Remote Sensing Change Detection from binary to semantic with SAM and CLIP - Wandong Jiang; Yuli Sun; Lin Lei; Gangyao Kuang; Kefeng Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Detecting changes without comparing images: Rules induced change detection in heterogeneous remote sensing images - Yuli Sun; Lin Lei; Zhang Li; Gangyao Kuang; Qifeng Yu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Retraction notice to “Synthesis and characterization of Hypsizygus ulmarius extract mediated silver nanoparticles (AgNPs) and test their potentiality on antimicrobial and anticancer effects” [Environ. Res. 235 (2023) 116671] - Kumar Manimaran; Dede Heri Yuli Yanto; Sita Heris Anita; Oktan Dwi Nurhayat; Kumar Selvaraj; Santhosh Basavarajappa; Mohamed Ibrahim Hashem; Govindasamy Palanisamy; Mei-Ching Lin; Keerthika Kumarasamy (Environmental Research, 2025)

Gestational Multi-metal Exposure in Relation to Anthropometric Birth Outcomes and Maternal Hormonal Profiles: A Deeper Insight Into Sex-Specific and Trimester-Specific Influences - Jinfeng Fu; Zhanlu Lv; Wenchao Zhu; Sisi Yu; Bingjun Lu; Xulong Chen; Chiqun Shan; Yuli Lin; Zhihong Huang; Yao Yao; Shaoyou Lu (Exposure and Health, 2025)

UAVs-UGV cooperative boom sprayer system based on swarm control - Yuli Chen; Zibo Liu; Zifeng Xu; Jianqin Lin; Xianlu Guan; Zhiyan Zhou; Dateng Zheng; Andrew Hewitt (Computers and Electronics in Agriculture, 2025)

Skin-printable, anti-freezing, and recyclable ionic hydrogel bioelectrode for continuous electrophysiological monitoring - Meiqiong Zheng; Leqi Li; Xinyuan Ye; Zichong Ji; Yuli Wang; Zonglei Wang; Shihong Lin; Mingzhe Wang; Wenqing Yan; Jiawei Yang; Pengcheng Zhou; Yujie Zhang; et al. (Chemical Engineering Journal, 2025)

Predicting the potential distribution of major marine mammals in the Cosmonaut Sea - Yufei Dai; Fanyi Meng; Fuxing Wu; Xing Miao; Denghui Yan; Mingding Zhong; Shunan Cao; Yuli Wei; Longshan Lin (Frontiers in Marine Science, 2025)
The Southern Ocean, a critical marine region on Earth, is undergoing significant environmental changes due to global climate change, including reductions in sea ice extent, ocean acidification, and alterations in the Antarctic Circumpolar Current (ACC). The Cosmonaut Sea, notable for its dynamic sea ice and rich biological activity, remains one of the least explored regions in the Southern Ocean, with limited data on its marine mammal populations. This study conducted during the 38th Chinese National Antarctic Research Expedition (CHINARE) from January to March 2022, collected systematic data on marine mammal occurrences. Species distribution modeling (SDM) was used to assess the influence of environmental variables on the distribution of the most abundant marine mammal species observed in the Cosmonaut Sea, including humpback whales ( Megaptera novaeangliae ), crabeater seals ( Lobodon carcinophaga ), and Antarctic minke whales ( Balaenoptera bonaerensis ). Our results indicated significant performance variations among the different algorithms, with ensemble model yielding more accurate predictions. Environmental variables such as water depth, sea surface height, and mixed layer thickness were identified as significant factors influencing habitat suitability for different species. Humpback whales were found to have the widest distribution range, followed by Antarctic minke whales and crabeater seals. Generally, the study provides the first comprehensive analysis of marine mammal distribution in the Cosmonaut Sea, highlighting the effectiveness of ensemble models in ecological predictions. The findings emphasize the importance of integrating high-resolution data and incorporating predator-prey interactions in future studies to improve our understanding and conservation of these complex ecosystems.

Experimental assessment of rigid surface collision effects on suspended ice particles - Zonghui Liu; Xueqin Bu; Guiping Lin; Ping Huang; Yuli Chen; Dongsheng Wen (Cold Regions Science and Technology, 2025)

Quantitative characterisation of microporous ceramic emitters microstructure and visualisation of seepage based on CT 3D reconstruction - Xuefei He; Pute Wu; Lin Zhang; Shoujun Wu; Xufei Liu; Fuhui Yang; Yuli Sun; Yiqian Wei (Biosystems Engineering, 2025)

Optimization by artificial neural network and modeling of ultrasound-assisted flavonoid extraction from Phyllanthus emblica L. based on deep eutectic solvents - Xiaolan Weng; Yuli Luo; Fei Pan; Huixin Pan; Zizhao Lao; Zuoyi Lin; Xiaolin Huang; Jiajun Xu; Xuwei Liu (Food Bioscience, 2025)

Regional sea level budget around Taiwan and Philippines over 2002‒2021 inferred from GRACE, altimetry, and in-situ hydrographic data - Wen-Hau Lan; Chi-Ming Lee; Chung-Yen Kuo; Li-Ching Lin; Eko Yuli Handoko (Journal of Geodesy, 2025)
The regional sea level budget and interannual sea level changes around Taiwan and Philippines are studied using altimetry, GRACE, and in-situ hydrographic data during 1993‒2021. Results show that the average sea level trend around Taiwan and Philippines during 1993–2021 derived from the altimetric data is 3.6 ± 0.2 mm/yr. Over 2002–2021, the study shows closure of sea level budget in the eastern ocean of Taiwan and Philippines within the observed data uncertainties, and the ocean mass accounts for 88%–100% of the observed sea level rise. In contrast, the sea level budget is not closed in the western ocean of Taiwan and Philippines, probably due to the lack of complete coverage by in-situ ocean observing systems. In addition, both regional sea level anomalies and their steric component around Taiwan and Philippines exhibit pronounced interannual and decadal variabilities. The trade wind stress associated with El Niño–Southern Oscillation and Pacific Decadal Oscillation offers a compelling explanation for the interannual and decadal signals of sea level anomalies in the southern ocean of Taiwan, with negative correlations of − 0.78 to − 0.64, indicating that trade wind stress makes a negative contribution to interannual-to-decadal sea level variability. In the northwestern ocean of Taiwan, the sea level variation is strongly influenced by the local monsoon system and shallow bathymetry with an annual amplitude of 90.3 ± 2.9 mm, larger than those in other regions around Taiwan and Philippines, where ocean mass is dominant with a high correlation with the sea level (+ 0.75 to + 0.78).

YY1 as a mediator to enhance the resistance of KRAS mutant colorectal cancer cells to cetuximab - Yi Ma; Yuli Hu; Yi Lin; Congying Wang; Yujie Lv; Wei Chen (Journal of Genetics, 2024)

Unveiling the green path: How urban openness reduces pollution and paves the way to sustainability - Chao Zhong; Hongbo Cai; Lin Liu; Rui Xue; Yuli Shan (Journal of Environmental Management, 2024)

Spatial and temporal distribution patterns of atmospheric PM2.5 and water-soluble inorganic ions in Shenzhen, China from 2016 to 2021 - Yuli Lin; Liuyi Yin; Xiaoheng Li; Yiming Ge; Zhihui Guo; Hongmei Qiu; Jiajia Ji; Shaoyou Lu (Chemosphere, 2024)

A novel variable discharge emitter for irrigation and salt-leaching - Xufei Liu; Lin Zhang; Yuli Sun; Xuanyue Tong; Xuefei He; Yiqian Wei (Biosystems Engineering, 2024)

Design, synthesis, X-ray crystal structure, and antimicrobial evaluation of novel quinazolinone derivatives containing the 1,2,4-triazole Schiff base moiety and an isopropanol linker - Lan Yang; Muhan Ding; Jun Shi; Na Luo; Yuli Wang; Dongyun Lin; Xiaoping Bao (Molecular Diversity, 2024)

Morphological convergence from independent crab lineages contributes to the flourishing symbiotic diversity between crabs and branching corals - Shaobo Ma; Zelin Chen; Yuli Sun; Meng Qu; Xin Wang; Wei Jiang; Geng Qin; Qiang Lin (Coral Reefs, 2024)

Occurrence of leaf spot caused by Colletotrichum plurivorum on cowpea in Fujian Province, China - Yuli Dai; Lin Gan; Xiaofei Liu; Chengzhong Lan; Zhiqiang Li; Xiujuan Yang (Crop Protection, 2024)

Similarity and dissimilarity relationships based graphs for multimodal change detection - Yuli Sun; Lin Lei; Zhang Li; Gangyao Kuang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

RETRACTED: Synthesis and characterization of Hypsizygus ulmarius extract mediated silver nanoparticles (AgNPs) and test their potentiality on antimicrobial and anticancer effects - Kumar Manimaran; Dede Heri Yuli Yanto; Sita Heris Anita; Oktan Dwi Nurhayat; Kumar Selvaraj; Santhosh Basavarajappa; Mohamed Ibrahim Hashem; Govindasamy Palanisamy; Mei-Ching Lin; Keerthika Kumarasamy (Environmental Research, 2023)

Optimization algorithm for determining working water head of subsurface irrigation with ceramic emitters based on soil wetting patterns - Xufei Liu; Lin Zhang; Chunhua Zhang; Yuli Sun; Xue Yang (Computers and Electronics in Agriculture, 2023)

Perchlorate in fine particulate matter in Shenzhen, China, and implications for human inhalation exposure - Quanzhi Zheng; Hongmei Qiu; Zhou Zhu; Weiran Gong; Duo Zhang; Jiaojiao Ma; Xin Chen; Jialei Yang; Yuli Lin; Shaoyou Lu (Environmental Geochemistry and Health, 2023)

Circ_0074027 regulates the progression of non-small cell lung cancer via miR-1304-5p/GJB2 axis - Jie Zhang; Yangli Zhu; Ya Lin; Yuli Hu; Zhijian Kuang (Molecular & Cellular Toxicology, 2023)

An Underwater Inductive Power Transfer System with a Compact Receiver and Reduced Eddy Current Loss - Zhengchao Yan; Chenxu Zhao; Qianyu Hu; Min Wu; Lin Qiao; Kehan Zhang; Yuli Hu (Journal of Marine Science and Engineering, 2022)
Inductive power transfer (IPT) technology is widely used in autonomous underwater vehicles (AUVs) to achieve safety and flexibility. However, the eddy current loss (ECL) will be generated in the seawater due to the high-frequency alternating current in the transmitter and receiver. An underwater IPT system with a series-none (SN) compensation topology is proposed in this paper to achieve a compact receiver for AUVs and reduce the ECL. The analytical model of the IPT system is built to analyze its transfer performance. The phase difference between the transmitter and receiver current of the SN compensation topology is larger than 90° compared to that of the conventional series-series (SS) topology, which can significantly decrease the magnitude of the electric field caused by coil currents; thus, the eddy current loss is reduced. Moreover, the optimal load resistance of the seawater IPT system is lower than that in the air, and the SN compensation topology has a more compact receiver with no compensation capacitor in the receiving side, which can save the internal space in the AUVs. An experimental prototype based on the SN topology is built, and the experimental results have verified the analysis.

Biotic and abiotic influences on monthly variation in carbon fluxes in on-year and off-year Moso bamboo forest - Yufeng Zhou; Guomo Zhou; Huaqiang Du; Yongjun Shi; Fangjie Mao; Yuli Liu; Lin Xu; Xuejian Li; Xiaojun Xu (Trees, 2019)

Sensitivity of Cochliobolus heterostrophus to three demethylation inhibitor fungicides, propiconazole, diniconazole and prochloraz, and their efficacy against southern corn leaf blight in Fujian Province, China - Yuli Dai; Lin Gan; Hongchun Ruan; Niuniu Shi; Yixin Du; Lei Liao; Zhixia Wei; Zhenyong Teng; Furu Chen; Xiujuan Yang (European Journal of Plant Pathology, 2018)

Effect of methane emission increases in East Asia on atmospheric circulation and ozone - Lin Shang; Yi Liu; Wenshou Tian; Yuli Zhang (Advances in Atmospheric Sciences, 2015)